Breast Cancer Screening Practice Among Patients and Nurses at Nishtar Hospital Multan (Medical Forum Monthly, 2024)
Objectives: To determine knowledge about breast cancer, breast cancer screening practices and risk factors of breast cancer among nurses and patients attending Nishtar Hospital, Multan.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at OPD and Nurses, Indoor of Nishtar Hospital, Multan from July 2016 to November 2016 Materials and Methods: Total participants were 253 and the data was collected by Convenient Sampling Method using structured questionnaire which were self-administered.Results: Total participants were 253, out of which 130 were nurses and 123 patients. 105(85%) pt. were married and 86(66.15%) nurses were unmarried. 86(69.9%) pt. and 115(88.5%) nurses had the H/O regular menstruation. 24(19.5%) pt. and 11(8.5%) nurses had positive H/O breast cancer.33(26.8%) pt. and 13(10%) nurses use contraceptives. 76(67.7%) pt. and 124 (95.4%) nurses had knowledge of breast cancer out of which 43(35%) pt. and 104(80%) nurses have knowledge of signs and symptoms. Audiovisual was commonest source of information for patients 36(29.3%),while 100(76.92%)nurses got to know about it during their training. 42(34.1%)pt. and 112(86.2%) nurses have good knowledge about BSE. 46(35.38%)nurses often perform BSE. 54(43.9%) pt. and115(88.5%) nurses had knowledge about CBE. 13(14.6%) pt 25(19.2%) nurses had CBE done. 10(8.1%) pt. and 21(16.2%)nurses ever had mammography and 101(82.1%) pt. and 113(86.9%) nurses considered it useful. Regarding risk factors of breast cancer, 86(69.9%) pt. and 112(86.2%) nurses considered positive family history, 31(25.2%) pt and 51(39.2%) nurses considered early menarche and 54(43.3%) pt. and 83(63.8%) nurses considered contraceptives as risk factors for breast cancer.Conclusions: It is concluded that majority of patients do not have adequate knowledge of breast cancer and its screening practices, and have many misconceptions regarding its risk factors. On the contrary, majority of nurses have proper Information of breast cancer, screening practices and its causative factors.